2015
DOI: 10.11606/issn.1678-4456.v52i1p48-56
|View full text |Cite
|
Sign up to set email alerts
|

Plasma rico em plaquetas autólogas na cicatrização do tendão do músculo gastrocnêmio de coelhos

Abstract: ResumoAs lesões tendíneas podem envolver a secção parcial ou total do tendão calcâneo comum e ocasionar alterações posturais do membro locomotor. O presente trabalho avaliou o efeito da aplicação tópica de concentrado de plaquetas autólogas na reparação do tendão do músculo gastrocnêmio de coelhos, decorridos 45 e 90 dias de período pós-operatório (PO). Doze coelhos adultos foram separados em dois grupos (n = 6) e submetidos à punção cardíaca e colheita de 10 mL de sangue para obtenção do plasma rico em plaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(17 reference statements)
0
3
0
3
Order By: Relevance
“…They also noted that the use of fibrin rich platelet arrays is an effective and safe strategy for accelerating tendon cell proliferation, stimulating type I collagen synthesis, and promoting neovascularization both in vitro and in vivo. Eurides et al (2015) also observed favorable results with the use of autologous PRP in the gastrocnemius muscle tendons of rabbits. Rumjantseva and Hoffmeister (2010) reported that a way of assessing the viability of stored platelets is pH determination.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…They also noted that the use of fibrin rich platelet arrays is an effective and safe strategy for accelerating tendon cell proliferation, stimulating type I collagen synthesis, and promoting neovascularization both in vitro and in vivo. Eurides et al (2015) also observed favorable results with the use of autologous PRP in the gastrocnemius muscle tendons of rabbits. Rumjantseva and Hoffmeister (2010) reported that a way of assessing the viability of stored platelets is pH determination.…”
Section: Introductionmentioning
confidence: 81%
“…However, according to Yamada et al (2012) calcium chloride is a weak platelet activator, with its main function being to antagonize the anticoagulant used, allowing the formation of gel. The activation, for example by thrombin, causes a change in the shape of the platelets, and subsequently, they develop pseudopodia, which promotes platelet aggregation and the subsequent release of granules containing growth factors through the open canalicular system (EVERTS et al, 2006). According to Wallace et al (1993), in order for platelets to be considered clinically effective, they must exercise a clotting function, i.e., prevent or stop bleeding.…”
Section: Daysmentioning
confidence: 99%
See 1 more Smart Citation
“…Após sua produção, o PRP deve apresentar uma concentração em torno de 1.000.000 de plaquetas/μL (Marx, 2004;Suaid et al, 2007;Barbosa et al, 2008). De acordo com Eurides et al (2015), concentrações superiores a 300.000 plaquetas μL-1 no sangue basal são suficientes para o preparo do PRP.…”
Section: Produção Do Prpunclassified
“…Tanto as plaquetas quanto o plasma, por terem fatores de crescimento (FCP), têm a função de iniciar o processo de cicatrização. O FCP tem atividades específicas no processo de reparação tecidual, estimulando a angiogênese, replicação tecidual, ação antiinflamatória, indução cicatricial e crescimento de novas estruturas, tendo assim grande importância em procedimentos cirúrgicos de reconstrução tecidual (EURIDES et al, 2015).…”
Section: Introducãounclassified